A pre–postintervention study to evaluate the impact of dose calculators on the accuracy of gentamicin and vancomycin initial doses - Hamad, Anas (BMJ Open, 2015)
OBJECTIVES: Gentamicin and vancomycin are narrow-therapeutic-index antibiotics with potential for high toxicity requiring dose individualisation and continuous monitoring. Clinical decision support (CDS) tools have been effective in reducing gentamicin and vancomycin dosing errors. Online dose calculators for these drugs were implemented in a London National Health Service hospital. This study aimed to evaluate the impact of these calculators on the accuracy of gentamicin and vancomycin initial doses. METHODS: The study used a pre–postintervention design. Data were collected using electronic patient records and paper notes. Random samples of gentamicin and vancomycin initial doses administered during the 8 months before implementation of the calculators were assessed retrospectively against hospital guidelines. Following implementation of the calculators, doses were assessed prospectively. Any gentamicin dose not within ±10% and any vancomycin dose not within ±20% of the guideline-recommended dose were considered incorrect. RESULTS: The intranet calculator pages were visited 721 times (gentamicin=333; vancomycin=388) during the 2-month period following the calculators’ implementation. Gentamicin dose errors fell from 61.5% (120/195) to 44.2% (95/215), p<0.001. Incorrect vancomycin loading doses fell from 58.1% (90/155) to 32.4% (46/142), p<0.001. Incorrect vancomycin first maintenance doses fell from 55.5% (86/155) to 33.1% (47/142), p<0.001. Loading and first maintenance vancomycin doses were both incorrect in 37.4% (58/155) of patients before and 13.4% (19/142) after calculator implementation, p<0.001. CONCLUSIONS: This study suggests that gentamicin and vancomycin dose calculators significantly improved the prescribing of initial doses of these agents. Therefore, healthcare organisations should consider using such CDS tools to support the prescribing of these high-risk drugs.